Estimation of effective moisture diffusivity of okra for microwave drying - Dadali, Gokce; Apar, Dilek Kihc; Ozbek, Belma (TAYLOR & FRANCIS INC, 2007)
The effect of microwave output power and sample amount on effective moisture diffusivity were investigated using microwave drying technique on round okra ( Hibiscus esculentus L.). The various microwave output powers ranging from 180 to 900W were used for the determination of effective moisture diffusivity for constant sample amount of 100 g okra. To examine the effect of sample amount on effective moisture diffusivity, the samples in the range of 25 - 100 g were dried at constant microwave output power of 360 W. By increasing the microwave output powers and decreasing the sample amounts, the effective moisture diffusivity values ranged from 20.52 x 10(-10) to 86.17 x 10(-10) and 34.87 x 10(-10) to 11.91 x 10(-9) m 2/ s(-1), respectively. The modeling studies were performed to illustrate the relationship between the ratio of the microwave output power to sample amount and effective moisture diffusivity. The relationship between drying constant and effective moisture diffusivity was also estimated.
Keywords: effective moisture diffusivity; microwave drying; round okra; MODEL; SLICES; Engineering